Psychometric analysis of the questionnaire for the detection of alcohol consumption - AUDIT in peruvian university students - Colán Herrera, Anel Cecilia (2022)
Alcohol consumption is a problem that has grown in the last 20 years in the world and a population that was affected is the youth, for this reason the present study proposes to analyze the psychometric evidence of the AUDIT in university students in Lima. The study is of instrumental design and the sampling applied was non-probabilistic by convenience. The results showed that the questionnaire presents adequate adjustment indexes, where X2/gl: 1.32, WRMR: 0.71, NFI: 0.99, CFI: 0.99, GFI: .99, AGFI: .98, RMSEA: 0.06, SRMR: 0.03 and TLI: 0.98, resulting adequate. A reliability of α=.86 and ω=.87 was found, and differences were identified in its use for the virtual and physical modalities. It is concluded that the AUDIT has optimal properties to assess excessive alcohol consumption.